Serum Iron Profile in Type 2 Diabetes Mellitus (Journal of Rangpur Medical College, 2023)
Background: Type 2 diabetes Mellitus is a major growing health issue worldwide. There is a strong relation between iron parameters and type 2 diabetes mellitus. Iron metabolism can directly or indirectly affect the occurrence and development of type 2 diabetes.Objectives: To observe serum levels in Type 2 Diabetes Mellitus patients.Methods: This cross sectional study was conducted from to in the Department of Physiology, Rangpur Medical College, Rangpur. For this study, total number of 150 subjects were selected among them 75 non-diabetic healthy subjects were included in group-A and 75 Type 2 Diabetes Mellitus patients were included in group-B. The subjects of group-A were selected from surrounding community of Rangpur district and subjects of Group-B were selected from Diabetic Association and from Outdoor of Endocrinology Department, Rangpur Medical College and Hospital, Rangpur. For statistical analysis independent sample “t”test was performed by computer based software SPSS- 23.0 version for windows.Results: Mean serum free iron concentration in Group A and Group B were 12.29±3.1 μmol/l and 15.24±6.8 respectively. Mean TIBC in Group A and Group B were 68.06±7.3 μmol/l and 56.89 ± 8.6 respectively. Mean serum ferritin concentration were 131±12.90 mg/ml and 170.50±15.1 respectively. The difference between serum iron, TIBC and ferritin between Group A and Group B were highly significant ( p _ 001 ).Conclusion: The results obtained from this study suggests that serum iron and serum ferritin were increased and TIBC was decreased in T2DM patients as compared to healthy control.J Rang Med Col. September 2023; Vol. 8, No. 2: 40-43